2001
DOI: 10.1385/bter:81:2:141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Effect of Dietary Selenium and Vitamin E on Some Antioxidant Enzyme Activities of Liver and Brain Tissues

Abstract: Since selenium and vitamin E have been increasingly recognized as an essential element in biology and medicine, current research activities in the field of human medicine and nutrition are devoted to the possibilities of using these antioxidants for the prevention or treatment of many diseases. The present study was aimed at investigating and comparing the effects of dietary antioxidants on glutathione reductase and glutathione peroxidase activities as well as free and protein-bound sulfhydryl contents of rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…In general, antioxidant defense systems eliminate reactive oxygen species (ROS) or other radical species to prevent oxidative stress, which is defined as an alteration in the steadystate balance between oxidant and antioxidant agents. It has been shown that under Se-deficient status, the activity of some antioxidative enzymes, such as GPx and CAT, the first line of cellular defense against potential oxidative damage [29], might be inhibited in various tissues, such as liver and muscle in poults [4], plasma in mice [30], and liver and brain of rat [31]. Consistent with previous studies, we observed decreased GPx, CAT, and Se in the Se-deficient group.…”
Section: Discussionsupporting
confidence: 90%
“…In general, antioxidant defense systems eliminate reactive oxygen species (ROS) or other radical species to prevent oxidative stress, which is defined as an alteration in the steadystate balance between oxidant and antioxidant agents. It has been shown that under Se-deficient status, the activity of some antioxidative enzymes, such as GPx and CAT, the first line of cellular defense against potential oxidative damage [29], might be inhibited in various tissues, such as liver and muscle in poults [4], plasma in mice [30], and liver and brain of rat [31]. Consistent with previous studies, we observed decreased GPx, CAT, and Se in the Se-deficient group.…”
Section: Discussionsupporting
confidence: 90%
“…Marked decreases in TrxR1 activity (2.2‐fold) and GSH levels and an enhancement of LP were observed, also by the others (Turan et al . ; Erkhembayar et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The element can also bind to amino acids forming low molecular species. A diet rich in Se (Turan et al 2001) ensures protection against free oxygen reactive species in tissues. Ingested Se can also bind to other toxic elements, as As, Cd, and Hg preventing their noxious action (Falandysz 2008).…”
Section: Cr Cu Se and Znmentioning
confidence: 99%